Extended genetic analysis of Brazilian isolates of Bacillus cereus and Bacillus thuringiensis - Viviane Zahner; Ana Carolina Telles de Carvalho e Silva; Gabriela Pinhel de Moraes; Douglas McIntosh; Ivano de Filippis (Memorias do Instituto Oswaldo Cruz, 2013)
Multiple locus sequence typing (MLST) was undertaken to extend the genetic characterization of 29 isolates of Bacillus cereus and Bacillus thuringiensis previously characterized in terms of presence/absence of sequences encoding virulence factors and via variable number tandem repeat (VNTR). Additional analysis involved polymerase chain reaction for the presence of sequences (be, cytK, inA, pag, lef, cya and cap), encoding putative virulence factors, not investigated in the earlier study. MLST analysis ascribed novel and unique sequence types to each of the isolates. A phylogenetic tree was constructed from a single sequence of 2,838 bp of concatenated loci sequences. The strains were not monophyletic by analysis of any specific housekeeping gene or virulence characteristic. No clear association in relation to source of isolation or to genotypic profile based on the presence or absence of putative virulence genes could be identified. Comparison of VNTR profiling with MLST data suggested a correlation between these two methods of genetic analysis. In common with the majority of previous studies, MLST was unable to provide clarification of the basis for pathogenicity among members of the B. cereus complex. Nevertheless, our application of MLST served to reinforce the notion that B. cereus and B. thuringiensis should be considered as the same species.